Understanding maternal choices and experiences of care by skilled providers: Voices of mothers who delivered at home in selected communities of Lusaka city, Zambia - Choolwe Jacobs; Charles Michelo; Adnan Hyder (Frontiers Media S.A., 2023)
BackgroundSignificant proportions of women living in urban areas including the capital cities continue to deliver at home. We aimed to understand why mothers in a selected densely populated community of Lusaka city in Zambia deliver from home without assistance from a skilled provider during childbirth.MethodsUsing a phenomenological case study design, we conducted Focus Group Discussions and In-depth Interviews with mothers who delivered at home without assistance from a skilled provider. The study was conducted between November 2020 and January 2021 among 19 participants. Data were analysed using content analysis.ResultsIndividual-related factors including the belief that childbirth is a natural and easy process that did not require assistance, lack of transport to get to the health facility, influence and preference for care from older women who were perceived to have the experience and better care, failure to afford baby supplies, and waiting for partner to provide the supplies that were required at the health facility influenced mothers' choices to seek care from skilled providers. Health system-related factors included mistreatment and disrespectful care such as verbal and physical abuse by skilled healthcare providers, stigma and discrimination, institutional fines, and guidelines such as need to attend antenatal care with a spouse and need to provide health facility demanded supplies.ConclusionIndividual and health system access related factors largely drive the choice to involve skilled providers during childbirth. The socioeconomic position particularly contributes to limited decision-making autonomy of mothers, thus, creating challenges to accessing care in health facilities. The health system-related factors found in this study such as mistreatment and disrespectful care suggests the need for redesigning effective and sustainable urban resource-limited context maternal health strategies that are culturally acceptable, non-discriminatory, and locally responsive and inclusive. Rethinking these strategies this way has the potential to strengthening equitable responsive health systems that could accelerate attainment of sustainable developmental goal (SDG) 3 targets.